An Analysis of Full Day School Policy - Sasmi Nelwati; Ulya Amelia; Melati Mandasari (Peneliti.net, 2020)
This study is aimed to identify how the implementation of full-day school programs in High Schools 3 and 8 Yogyakarta. This research is related to policies due to changing times. The approach used is a qualitative case study. Data collection techniques are observation, interviews, and documentation. The subjects of this study were the school principal, deputy headmaster, educators, education staff, BK teachers, students, and graduates. The findings show that a full-day school creates conflict for schools and makes schools adapt to new rules